Globalization, minorities, and civil society perspectives from Asian and Western cities - Hasegawa, Koichi; Yoshihara, Naoki (Stratification and inequality series, 2008)
One effect of globalization has been urban restructuring in various cities of Asia, increasing migration from Asia to European cities, and the intensification of debates about citizenship. The multi-dimensional constellations of ethnic minorities in Asian and European cities have become increasingly divided, stratified, and segmented. The post-colonial legacy permeates these phenomena. This book examines developments in Asia and Europe on the basis of fieldwork surveys, examining anti-globalization movements and minority group dissent at the local level, and their effects on civil society. Chapters include studies of the homeless in Manila, Thai-Chinese residents in Bangkok, Islam in Bali, and the Bangladesh community in London.